Analisis inflasi di lihat dari permintaan dan penawaran di Indonesia Tahun 2000-2018 - Desy Martauli; Amri Amir; Candra Mustika (e-Journal Perdagangan Industri dan Moneter, 2020)
This study aims to determine the analysis of inflation in terms of demand and supply in Indonesia in 2000-2018, the variables studied are the exchange rate, loan interest rates, world oil prices, public consumption. The type of time series data with the analytical method used in this study is using simple linear regression analysis and multiple linear regression (OLS) methods. The results of the trend of each variable inflation, exchange rate, interest rates on loans, world oil prices and public consumption fluctuate and have a tendency to increase with average inflation of 2.71%, the exchange rate of Rp. 14,143, the loan interest rate of 12.15%, the price of world oil is 91.67% and Indonesian people's consumption is 6,850,384 billion rupiah. The results of simple linear regression and multiple linear regression are shown through the simultaneous test (F test) that the exchange rate, loan interest rate, world oil price, and public consumption have a positive and significant effect on inflation in Indonesia. The results of the partial test (t-test) show that the loan interest rate and world oil prices have a positive and significant effect on inflation in Indonesia and public consumption has a negative and significant effect on inflation in Indonesia, while the exchange rate has a positive and significant effect on inflation in Indonesia. Keywords: Inflation, Exchange rate, Loan interest rate, World oil price, Community consumption